Monitoring of Bolted Steel Plate Joints for Torque Loss and Corrosion: A Guided Wave Approach - Shah, Jay Kumar (Curtin University, 2021)
Bolted steel structures offer sustainable solutions to the construction industry. These can be quickly built and efficiently recycled if maintained efficiently. However, steel joints are prone to the challenges of bolt loosening and corrosion during their service period. This thesis reports the original findings on the technology which can be developed to monitor the bolted structures in an automated and non-invasive manner.